Low power portable bioelectronics holter monitor for arrhythmias detection - Tan, Hock Meng (2014)
Holter monitor also known as ambulatory electrocardiography device is a medical tool commonly use by cardiologist around the world to conduct 24- 48 hours constant monitoring of electrocardiogram (ECG) signal for heart disease patient. Multiple electrodes will be connected to the patient chest using adhesive and then link to the monitor for recording purpose. Through the device, doctor will be able to diagnose any possible heart symptom and be alert first hand on their communication devices should there be any emergency case.